Mussel-inspired polydopamine chemistry to modulate template synthesis of 1D metal–organic framework superstructures. Issue 43 (29th October 2018) - Yu, Boxuan; Ye, Gang; Zeng, Zhen; Zhang, Lei; Chen, Jing; Ma, Shengqian
Abstract : Novel contra-diffusion synthesis of diverse 1D MOF superstructures in the channels of polycarbonate track-etched membranes regulated by a substrate-involving catalytic transesterification mechanism or mediated by mussel-inspired polydopamine chemistry. Abstract : Mussel-inspired polydopamine (PDA) chemistry was exploited, for the first time, to regulate the contra-diffusion synthesis of 1D metal–organic framework (MOF) superstructures in the channels of polycarbonate track-etched membranes. The PDA modified template channels facilitate controllability for the heterogeneous nucleation and interfacial growth of various MOFs. Well-defined 1D hybrid MOF nanotubes with a high aspect ratio up to 40 and length of 10 μm were successfully obtained. Potential application of the composite membrane for decontamination of organic dyes was demonstrated by a facile filtration method. This study provides new insights into the surface chemistry directed growth behavior of MOFs on polymeric templates. Moreover, the methodology of PDA chemistry mediated contra-diffusion synthesis opens a new avenue to fabricate diverse 1D superstructures of MOFs and other functional materials.